From computer ethics to the ethics of global ICT society - Gorniak-Kocikowska, Krystyna (Library Hi Tech, 2007)
Purpose - The purpose of this paper is to address the place of computer/ICT ethics in the global ICT society driven by knowledge economy. Design/methodology/approach - The paper focuses on three main issues: the evolution of the name of the leading technology of our times and, accordingly, the evolution of the name of the society in which this technology plays the leading role; some ethical dilemmas that the global ICT society will need to solve; global ICT ethics and the knowledge economy. Findings - The paper suggests that global ICT ethics should be an ethics focusing on the dynamics of the relationship between the weak and the strong, the rich and the poor, the healthy and the sick worldwide - and it should explore the ethical problems from the point of view of both parties involved. That way, Global ICT Ethics can have a truly communicative character, and it can become an ethics that will be both a co-creator and also a result of a democratic processes. Originality/value - This paper should interest anyone concerned with ICT and globalization.
Keywords: Communication technologies; Ethics; Globalization; dept.phi; peer-reviewed